Gambaran Tingkat Caregiver Burden pada Keluarga dengan Anak Cerebral Palsy Usia 0-12 Tahun di Bandung Raya - Amanda Dwi Fortuna; Udin Rosidin; Adelse Prima Mulya (Universitas Malahayati Lampung, 2026)
ABSTRACT Cerebral palsy is a non-progressive neurodevelopmental disorser causing long-term motr impairment in children and requiring ongoing care, placing families at risk of cargiver burden across physical, emotional, social, financial, and family relationships domains. This quantitative descriptive study aimed to describe the level of caregive burden among families of children with cerebral palsy in Greater Bandung Area. A total of 142 caregivers of children aged 0-12 years, members of Komunitas Keluarga Cerebral Palsy, were selected using stratified random sampling. The instrument used was the Zarit Burden Interview (22 items), which has been translated and tested for validity and reliability. The results showed that the level of caregiver burden in most caregivers (58.5%) was in the mild-moderate category, with the financial burden as the heaviest burden category (40.8%). The physical aspect was dominated by the mild-moderate (39.4%) and moderate-heavy (38.7%) burden categories. The majority of caregivers experience mild to moderate emotional burden (57%), while the majority experience no burden or mild burden in terms of social aspects (44.4%). In terms of family relationships, mild to moderate burden is the most common category (66.9%). These findings indicate the potential role of social support from the community in reducing the burden of caregiving. Responsive social support for caregivers' needs, such as home visit services, respite care, and psychological support from health workers, needs to be strengthened continuously and adjusted to the level of caregiver burden, especially to reduce the burden on the financial and physical aspects. Keywords: Caregiver Burden, Cerebral Palsy, Family, Greater Bandung Area. ABSTRAK Cerebral palsy merupakan gangguan neurodevelopmental non-progresif yang menyebabkan disabilitas motorik jangka panjang pada anak. Anak dengan cerebral palsy memerlukan perawatan yang kompleks dan berkelanjutan, sehingga keluarga sebagai pengasuh utama berisiko mengalami caregiver burden yang mencakup aspek fisik, emosional, sosial, finansial, dan hubungan dalam keluarga. Penelitian ini bertujuan menggambaran tingkat caregiver burden pada keluarga anak cerebral palsy di Bandung Raya. Penelitian ini menggunakan desain deskriptif kuantitatif dengan 142 caregiver anak cerebral palsy usia 0-12 tahun yang tergabung dalam Komunitas Keluarga Cerebral palsy, dengan teknik stratified random sampling. Instrumen yang digunakan adalah Zarit Burden Interview (22 item) yang telah diterjemahkan dan teruji valid dan reliabel untuk digunakan. Hasil penelitian menunjukkan tingkat caregiver burden pada sebagian besar atau 83 caregiver (58,5%) berada pada kategori beban ringan-sedang, 34 caregiver (23,9%) merasakan beban sedang-berat, 20 responden (14,1%) merasa tidak ada beban/beban ringan, dan 5 responden (3,5%) merasakan beban pengasuhan yang berat. Temuan ini menunjukkan kemungkinan peran dukungan sosial dari komunitas dalam menekan beban pengasuhan. Dukungan sosial yang responsif terhadap kebutuhan kebutuhan caregiver, seperti layanan home visit, respite care, dan dukungan psikologis oleh tenaga kesehatan, perlu diperkuat secara berkelanjutan dan disesuaikan dengan tingkat beban caregiver, terutama untuk menurunkan beban pada aspek finansial dan fisik. Kata Kunci: Bandung Raya, Cargiver Burden, Cerebral Palsy, Keluarga.